Mineralogy of the Hydrothermal Alteration in the Námafjall Geothermal Field (Iceland) - Albert Mínguez, Helena; Ortega, L.; Lunar, Rosario; Martínez-Frías, J.; Piña, Rubén (Sociedad Española de Mineralogía, 2011)
Present-day rift zones in Iceland commonly develop high-temperature geothermal systems related to central volcanoes (Trønnes, 2003). This study was developed at the high-temperature geothermal field of Námafjall, located at the Iceland Northern Rift Zone, near the Krafla central volcano. In this area, the constant hydrothermal activity alters Pleistocene hyaloclastites sequences and Holocene lavas and scoria cones especially to clay minerals. Different degrees of alteration, anisotropic distribution of fissures, faults and permeable zones, and accumulation of different minerals, generates a spotty distribution of red, brown, yellow, pink and white patches, reflecting the mosaic character of hydrothermal alteration (Geptner et al., 2005, 2007). A detailed mineralogical study of the altered volcanic rocks from the outer edge of the Námafjall geothermal field has been carried out in order to determine the surface alteration processes associated with geothermal activity, inferring pH conditions and, where appropriate, the temperature of the alteration processes. Peer reviewed